Мембранний механізм як нова складова розвитку анемії при злоякісних новоутвореннях травного каналу - Гуніна, Л.М.; Сорокін, Б.В.; Коробко, В.Б.; Олійник, С.А.; Войціцький, В.М.; Гуменюк, Р.С.; Савоста, А.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The complex analysis of the obtained findings as for the changes of indices of a structural-and-functional status of membranes of erythrocytes in cancer patients with anemia, one of the main parameters of which is the content of intraerythrocytic haemoglobin, is perfomed. The convincing evidence for the changes of the levels of main membrane lipids, spectrin and ankirin, quantitative and qualitative changes of lipids with accumulation of their oxidized forms in fluorescent probing, and lipid-protein spatial interrelations in membranes is presented. Alongside with the essential changes of functional properties of membranes of red blood cells and the availability of significant correlation relations between the above-mentioned parameters of membrane states as for the content of intraerythrocytic haemoglobin, the obtained data indicate the availability of a new aspect of the anemia development in patients with malignancies mediated by membrane disorders.